Pelaksanaan dan Pendampingan Senam Hamil sebagai Upaya dalam Mempersiapkan Persalinan yang Aman dan Sehat di Desa Bori Kamase, Maros - Linda Hardianti Saputri; Nurhayati Nurhayati; Sitti Hadriyanti Hamang (Jurnal Pengabdian Pada Masyarakat, 2021)
IMPLEMENTATION AND ASSISTANCE OF PREGNANCY AS A PREPARATION FOR SAFE AND HEALTHY LABOR IN BORIKAMASE VILLAGE, MAROS. Midwives are recognized as responsible and accountable professionals who work as partners for women to provide support, care and advice during pregnancy. Care that includes prevention, promotion of normal delivery, detection of complications in mother and child and access to medical assistance or other appropriate assistance. Pregnant exercise during pregnancy can increase birth weight and reduce the incidence of preterm and delivery complications. One of the interventions that can be done is physical exercise, because it has a positive effect on the fetus, pregnancy, birth weight and maternal health and reduces labor complications such as prolonged labor and reduces pain levels. One of the physical exercises that can be done during pregnancy is pregnancy exercise. Through the pregnancy exercise training provided, it is hoped that pregnant women can independently practice the practice of pregnancy exercises at home regularly as an effort to prepare for a safe and healthy delivery so as to prevent possible complications that can arise during the labor process. This activity was carried out in Putu Lekoala, Borikamase Village, Maros Baru Subdistrict with the Lecture Method, discussion and direct mentoring for Pregnant Exercise Practices. The results of this activity show the enthusiasm of pregnant women to participate in this activity and practice the pregnancy exercise movements that are taught where pregnant women can re-practice the movements that have been obtained properly and correctly and the enthusiasm of pregnant women is seen in this pregnancy exercise.